2019
DOI: 10.18203/2320-1770.ijrcog20191186
|View full text |Cite
|
Sign up to set email alerts
|

Effect of perineal massage in the second stage of labour, on the incidence of episiotomy and perineal tears

Abstract: Background: This study aimed to investigate whether perineal massage during second stage of labour could decrease perineal trauma in the form of episiotomy and perineal tears.Methods: One hundred and fifty term antenatal women in labour were randomly assigned to two groups, one of which received perineal massage and the other received routine care during the second stage. Frequency of episiotomies, perineal tears, intact perineums, degrees of perineal tears, duration of second stage of labour and perineal pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(42 citation statements)
references
References 7 publications
3
39
0
Order By: Relevance
“…Again the current findings are matched with Raja, et al (2019) (30) reported that, the mean duration of 2 nd stage of labor in the massage group was significantly shorter than in the control group. Furthermore, (31) in Egypt conducted randomized controlled trial, reported a highly statistically significant reduction the average duration of the 2 nd stage of labor in the perineal massage and kegel exercise group compared to the control group.…”
Section: Discussionsupporting
confidence: 91%
“…Again the current findings are matched with Raja, et al (2019) (30) reported that, the mean duration of 2 nd stage of labor in the massage group was significantly shorter than in the control group. Furthermore, (31) in Egypt conducted randomized controlled trial, reported a highly statistically significant reduction the average duration of the 2 nd stage of labor in the perineal massage and kegel exercise group compared to the control group.…”
Section: Discussionsupporting
confidence: 91%
“…Result presented as forest plot shown in figure 4, it was significantly lower the risk of second-degree perineal tear (RR: 1.05, 95% CI 0.9-1.22, p= 0.66) compared to control group without heterogeneity (I 2 =0%). Third degree perineal tear: Five studies reported third-degree perineal tear outcomes (14,15,(21)(22)(23). Result presented as forest plot shown in figure 5, it was significantly lower the risk of third-degree perineal tear (RR: 0.61, 95% CI 0.06-6.59, p= 0.66) compared to control group without heterogeneity (I 2 =38%).…”
Section: Meta-analysismentioning
confidence: 94%
“…Because of the statistical heterogeneity among the included studies were less than 50% (I 2 =0%, p =0.37), fixed effects model was used for pooled analysis. First degree perineal tear: Risk of first-degree perineal tear was reported in eight studies (14)(15)(16)(17)(18)(21)(22)(23). Meta-analysis findings indicated (Figure 3) lower the risk of first-degree perineal tear (RR: 1.20, 95% CI 0.90-1.59 p=0.13) compared to control group with considerable heterogeneity [I 2 =37%].…”
Section: Meta-analysismentioning
confidence: 99%
See 2 more Smart Citations